Dimensions of student success: a framework for defining and evaluating support for learning in higher education. Issue 5 (29th July 2019) - Lane, Murray; Moore, Alison; Hooper, Louise; Menzies, Victoria; Cooper, Bernadine; Shaw, Natasha; Rueckert, Caroline
ABSTRACT: The capabilities students need for success during and beyond higher education extend far beyond specific discipline skills to include the development of productive mindsets, the management of life circumstances and the way they relate to others and identify with their profession. The provision of support for these capabilities at university can be both diverse in scope and diffuse in delivery. Consequently, the development of streamlined and integrated evaluation strategies to measure the extent to which these capabilities are being successfully delivered can be challenging. This paper describes how one Australian university used a collaborative process to design an evaluation framework for student learning services. The framework, a first for this university, represents the breadth of student support, including a typology of support for learning: connectedness, mindsets, self-management, professional identity and academic capabilities. These terms, coined as dimensions, form the scaffold of university-wide delivery of support for learning initiatives.